2016
DOI: 10.1038/nn.4331
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-responsive neurons of the paraventricular thalamus control sucrose-seeking behavior

Abstract: Feeding behavior is governed by homeostatic needs and motivational drive to obtain palatable foods. Here, we identify a population of glutamatergic neurons in the paraventricular thalamus, which express the glucose transporter Glut2 (Scl2a2) and project to the nucleus accumbens. These neurons are activated by hypoglycemia and, in freely moving mice, their activation by optogenetics or Slc2a2 inactivation increases motivated sucrose but not saccharin-seeking behavior. These neurons may control sugar overconsump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
134
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(145 citation statements)
references
References 21 publications
10
134
1
Order By: Relevance
“…This discrepancy could be due to differences in the species used in these experiments. Also, in our experiments, the reduction in GLUT2 expression was limited to ependymal cells and tanycytes, while in the transgenic line, expression was also affected in neurons sensitive to hypoglycemia located in the brainstem (Tarussio et al, 2014) or neurons in the thalamus involved in carbohydrate preference (Labouebe et al, 2016). We also showed that suppression of GLUT2 expression in tanycytes leads to the loss in response to increased icv glucose, supporting a role for indirect control of glucose over the expression of neuropeptides that control hunger and satiety.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…This discrepancy could be due to differences in the species used in these experiments. Also, in our experiments, the reduction in GLUT2 expression was limited to ependymal cells and tanycytes, while in the transgenic line, expression was also affected in neurons sensitive to hypoglycemia located in the brainstem (Tarussio et al, 2014) or neurons in the thalamus involved in carbohydrate preference (Labouebe et al, 2016). We also showed that suppression of GLUT2 expression in tanycytes leads to the loss in response to increased icv glucose, supporting a role for indirect control of glucose over the expression of neuropeptides that control hunger and satiety.…”
Section: Discussionmentioning
confidence: 47%
“…However, those that exist have been corroborated by the use of mice expressing a fluorescent reporter gene (eYFP) under the control of the GLUT2 promoter, GLUT2‐eYFP mice (Mounien et al, 2010). GLUT2 was found in neurons and astrocytes dispersed in many structures, including the hypothalamus, the brain stem, the thalamic area (Arluison, Quignon, Thorens, Leloup, & Penicaud, 2004; Labouebe, Boutrel, Tarussio, & Thorens, 2016) and in tanycytes (Garcia et al, 2003). Tanycytes are radial glial‐like cells surrounding the lateral walls of the infundibular recess (Recabal, Caprile, & Garcia‐Robles, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…4c). PVT is involved in motivated behaviours 36 including feeding 37,38 , and AgRP →PVT stimulation induces feeding 35 . Using CRACM, we found that BLA →InsCtx neurons and BLA inhibitory interneurons received synaptic input from PVT (Extended Data Fig.…”
Section: A Pathway From Agrp Neurons To Insctxmentioning
confidence: 99%
“…Feeding is likely regulated by these neurons because they are a source of inhibitory drive onto downstream, possibly orexigenic, hypothalamus neurons (Castro et al, 2015;Zheng et al, 2007). Much less is known about how inputs to the NAc influence consummatory behavior, although there is increasing interest in this topic (Do-Monte et al, 2017;Labouè be et al, 2016;Parker et al, 2015;Tellez et al, 2016).…”
Section: Nac Involvement In Feeding Behaviormentioning
confidence: 99%